The FGF23/α-Klotho Axis in Postmenopausal Osteoporosis: Associations with Bone Mineral Density and Diagnostic Discrimination - Mete Hakan Karalok; Naile Fevziye Misirlioglu; Oznur Dundar Akin; Hafize Uzun (Journal of Clinical Medicine, 2026)
Background: Fibroblast growth factor 23 (FGF23) and α-Klotho are key regulators of mineral metabolism and bone homeostasis; however, their combined diagnostic value in postmenopausal osteoporosis remains incompletely understood. This study investigated the associations of serum FGF23, α-Klotho, and the FGF23/α-Klotho ratio with bone mineral density (BMD), bone turnover markers, and their diagnostic performance for postmenopausal osteoporosis. Methods: This cross-sectional study included 165 women divided into three groups: premenopausal healthy controls (n = 55), postmenopausal non-osteoporotic women (n = 55), and postmenopausal women with osteoporosis (n = 55). Serum FGF23 and α-Klotho concentrations were measured by enzyme-linked immunosorbent assay. Bone mineral density was assessed by dual-energy X-ray absorptiometry. Correlation analyses, age- and BMI-adjusted partial correlations, multivariable linear and logistic regression analyses, receiver operating characteristic (ROC) analyses, and incremental diagnostic models were performed. Diagnostic ROC and incremental model analyses were restricted to postmenopausal women (n = 110). Results: Serum FGF23 concentrations and the FGF23/α-Klotho ratio increased progressively across the study groups, whereas α-Klotho levels decreased (all p < 0.001). FGF23 was inversely correlated with lumbar spine, femoral neck, and total hip BMD and T-scores (all p < 0.001), whereas α-Klotho demonstrated positive correlations with all BMD parameters (all p < 0.001). These associations remained significant after adjustment for age and BMI. In multivariable linear regression analyses, the FGF23/α-Klotho ratio showed the strongest independent association with skeletal T-scores (standardized β = −0.379 to −0.404; all p < 0.001). Multivariable logistic regression identified lower 25-hydroxyvitamin D, higher parathyroid hormone, higher FGF23, and lower α-Klotho as independent factors associated with osteoporosis. In analyses restricted to postmenopausal women, the FGF23/α-Klotho ratio showed the highest numerical discriminative performance for osteoporosis (AUC = 0.832, 95% CI: 0.755–0.901), followed by α-Klotho (AUC = 0.793) and FGF23 (AUC = 0.697). The ratio significantly outperformed FGF23 alone (ΔAUC = 0.135, p = 0.001), whereas its performance did not differ significantly from that of α-Klotho (ΔAUC = 0.038, p = 0.270). Adding FGF23 and α-Klotho to age, BMI, and 25-hydroxyvitamin D increased the AUC from 0.743 to 0.882. Conclusions: Serum FGF23 and α-Klotho are independently associated with bone mineral density and are linked to bone turnover markers in postmenopausal women. The FGF23/α-Klotho ratio showed the highest numerical discriminative performance among the evaluated biomarkers, although its performance was not significantly different from that of α-Klotho alone. The combined assessment of FGF23 and α-Klotho provided additional discriminatory information beyond the measured clinical variables. Given the cross-sectional design and lack of external validation, these findings should be considered exploratory and require validation in prospective independent cohorts.